Development of E-Module Biology Based on Modified Free Inquiry on Invertebrate Materials as Independent Teaching Material - Khoirun Najah; Runtut Prih Utami (Proceeding International Conference on Religion, Science and Education, 2023)
This research aims to develop biology E-Module Based Modified Free Inquiry on Invertebrate Main Subject as independent teaching materials and measure E-Modul quality. This reaserch is determined as a Research and Development (R&D) method by applying ADDIE procedure which is focused on the level of Analysis, Design, Development and Evaluation phases. It employs questionnaire as a research instrument. Biology E-Modul quality is assesed by some respondents involving in this research. They are, one subject expert, one media professional, three peer reviewers, three biology teachers, and fifteen students’ responses of X MIPA MA WI Kebarongan Banyumas. The data obtained from the research is analized by implementing qualitative and quantitaive decriptive method. Biology E-Module product based modified free inquiry is developed using ADDIE model on main subject’s sub material about Invertebrate for students in the first year of X MIPA MA WI Kebarongan Banyumas. The result of this research shows that e-modul product has a great quality with a precentage of 81,67% (one subject expert), 92,27% (one media professional), 87,36% (peer reviewers), 89,92% (three biology teachers) and 93,52 % (fifteen students’ responses). Thus, it can be concluded that Biology E-module has a great quality to be used as independent teaching materials to the students of X MIPA MA WI Kebarongan Banyumas.